Application of modified Asimov's laws to the agent of home service robot using state, operator, and result (Soar). (7th June 2018) - Van Dang, Chien; Jun, Mira; Shin, Yong-Bin; Choi, Jae-Won; Kim, Jong-Wook
This study aims to interpret and apply Asimov's Three Laws of Robotics to home service robots. An agent is developed herein with the ability to focus its attention on human beings' health, particularly the elderly and the diseased, by delivering food. The agent is developed on a cognitive agent architecture, state, operator, and result (Soar), to enable effective reasoning and decision-making skills. This study deals with basic home care services, such as food delivery and emergency response; therefore, common food care and emergency rules are newly proposed based on the priority values that correspond to a family's circumstances and/or emergency levels. Asimov's Three Laws are modified to aid the home service robot to follow a predetermined order in selecting a food item or recommending an alternative food item suitable for its user's prevailing health condition. Experimental results confirm that reasoning and decision-making of the proposed agent are logically and ethically valid for a home service robot and ensure compliance with both the original and modified Asimov's Three Laws.